Chemistry and Ecology - Chemistry and Ecology (Taylor & Francis, 2026)
Chemistry and Ecology publishes original articles, short notes, registered reports and occasional reviews on the relationship between chemistry and ecological processes. This journal reflects how chemical form and state, as well as other basic properties, are critical in their influence on biological systems and that understanding of the routes and dynamics of the transfer of materials through atmospheric, terrestrial and aquatic systems, and the associated effects, calls for an integrated treatment. Chemistry and Ecology will help promote the ecological assessment of a changing chemical environment and in the development of a better understanding of ecological functions.
FI 0.41
Q3
Keywords: Chemistry; Acuerdos transformativos; Transformative agreements; Química ambiental; Ecología; Contaminación ambiental; Biogeoquímica; Ecosistemas